American justice 2014 nine clashing visions on the Supreme Court - Epps, Garrett (Univ. of Pennsylvania Press, 2014)
"Garrett Epps reviews the key decisions of the 2013-2014 Supreme Court term, highlighting one opinion or dissent from each Justice to illuminate the political and ideological views that prevail on the Court" ... Book Jacket